Phenotypic plasticity in the cold tolerance of three populations of the salvinia weevil (Cyrtobagous salviniae) from Louisiana, USA. Issue 9 (2nd September 2019) - Cozad, Allie; Diaz, Rodrigo; Mudge, Christopher
ABSTRACT: We compared the cold tolerance of three populations of the salvinia weevil, Cyrtobagous salviniae . When exposed to 0°C, lethal time to kill 90% of adults from the Bayou Nicholas population was greater than the Houma and Natchitoches populations. This weevil exhibited phenotypic plasticity which could be used in mass rearing.